PENERAPAN METODE POLYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III PADA MATERI MEMECAHKAN MASALAH SOAL CERITA POKOK BAHASAN PECAHAN DI SDN MERJOSARI III KOTA MALANG - Moh. Maulidil Alif; Anwar, Moh. Farid Nurul; Chotimah, Chusnul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of students in solving word problems on fraction material and the limited ability of students to understand the steps of problem solving systematically. In addition, the teacher-centered learning process caused students to be less actively involved in learning activities, resulting in suboptimal understanding of mathematical concepts. In fact, learning that emphasizes thinking processes and problem solving can help students understand mathematical concepts more deeply. This study aimed to improve students’ learning outcomes through the application of the Polya method in solving fraction word problems. The method used was Classroom Action Research (CAR) with the Kemmis and McTaggart model conducted in two cycles, consisting of planning, action, observation, and reflection stages. The research subjects were 27 third-grade students at SDN Merjosari III Kota Malang. Data were collected through learning outcome tests, observation, and documentation. The data were analyzed using descriptive quantitative and qualitative approaches by calculating the mean scores and the percentage of classical learning mastery. The results showed that the application of the Polya method was able to improve students’ learning outcomes. The percentage of learning mastery increased from 51.85% in Cycle I to 85.19% in Cycle II, accompanied by an increase in the class average score. Therefore, the Polya method is effective in improving students’ ability to solve fraction word problems and helping students think systematically in mathematics learning.